Analysis of shape and location effects of closely spaced metal loss defects in pressurised pipes - Al Owaisi, S.S.; Becker, Adib A.; Sun, Wei (Elsevier, 2016)
Metal loss due to corrosion is a serious threat to the integrity of pressurised oil and gas transmission pipes. Pipe metal loss defects are found in either single form or in groups (clusters). One of the critical situations arises when two or more defects are spaced close enough to act as a single lengthier defect with respect to the axial direction, causing pipe ruptures rather than leaks, and impacting on the pressure containing capacity of a pipe. There have been few studies conducted to determine the distance needed for defects to interact leading to a failure pressure lower than that when the defects are treated as single defects and not interacting. Despite such efforts, there is no universally agreed defect interaction rule and pipe operators around the world have various rules to pick and choose from. In this work, the effects of defect shape and location on closely spaced defects are analysed using finite element analysis. The numerical results showed that defect shapes and locations have a great influence on the peak stress and its location as well as the failure pressure of pipes containing interacting defects.